Antiartherosclerotic effects of plant flavonoids - Salvamani, Shamala; Gunasekaran, Baskaran; Shaharuddin, Noor Azmi; Ahmad, Siti Aqlima; Shukor, Mohd Yunus (Hindawi Publishing Corporation, 2014)
Atherosclerosis is the process of hardening and narrowing the arteries. Atherosclerosis is generally associated with cardiovascular diseases such as strokes, heart attacks, and peripheral vascular diseases. Since the usage of the synthetic drug, statins, leads to various side effects, the plants flavonoids with antiartherosclerotic activity gained much attention and were proven to reduce the risk of atherosclerosis in vitro and in vivo based on different animal models. The flavonoids compounds also exhibit lipid lowering effects and anti-inflammatory and antiatherogenic properties. The future development of flavonoids-based drugs is believed to provide significant effects on atherosclerosis and its related diseases. This paper discusses the antiatherosclerotic effects of selected plant flavonoids such as quercetin, kaempferol, myricetin, rutin, naringenin, catechin, fisetin, and gossypetin.